Selection of Multidrug-Resistant Bacteria in Medicated Animal Feeds - Brown, Emily E. F.; Cooper, Ashley; Carrillo, Catherine; Blais, Burton (Frontiers in Microbiology, 2019)
Exposure to antimicrobial resistant (AMR) bacteria is a major public health issue which may, in part, have roots in food production practices that are conducive to the selection of AMR bacteria ultimately impacting the human microbiome through food consumption. Of particular concern is the prophylactic use of antibiotics in animal husbandry, such as the medication of feeds with sulfonamides and other antibiotics not considered clinically relevant, but which may nonetheless co-select for multi-drug resistant bacteria harbouring resistance to medically-important antibiotics. Using a multi-drug resistant Klebsiella pneumoniae strain exhibiting resistance to sulfonamides and beta-lactams (including carbapenem) as a model, we examined the ability of non-medicated and commercially-medicated (sulfonamide) animal feeds to select for the model strain when inoculated at low levels by measuring its recovery along with key AMR markers, sul1(sulfonamide) and blaKPC-3 (meropenem), under different incubation conditions. When non-medicated feeds were supplemented with defined amounts of sulfadiazine the model strain was significantly enriched after incubation in Mueller Hinton Broth at 37oC overnight, or in same at room temperature for a week, with consistent detection of both the sul1 and blaKPC-3 markers as determined by polymerase chain reaction (PCR) techniques to screen colony isolates recovered on plating media. Significant recoveries of the inoculated strain and the sul1 and blaKPC-3 markers were observed with one of three commercially-medicated (sulfamethazine) feeds tested under various incubation conditions. These results demonstrate that under certain conditions the prophylactic use of so-called non-priority antibiotics in feeds can potentially lead to co-selection of environmental AMR bacteria with resistance to medically important antibiotics, which may have far-reaching implications for human health.